COMPETITION EXPERIENCE, RELATIVE AGE EFFECT AND AVERAGE AGE OF THE SENIOR WORLD EVENTS’ MEDAL-WINNING BASKETBALL PLAYERS - ZILINYI, Zsombor; NAGY, Ágoston; STERBENZ, Tamás (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2020)
The International Basketball Federation (FIBA) has changed its youth competition system in 2004, and due to this regulation, many players had the chance to compete every year at youth level and later, to elevate to the top. The purpose of our study was to inspect those medal-winning European basketball players who competed in the past 19 senior basketball world events. We analysed the tendencies of selection by dissecting the set-up of successful senior national teams. We investigated each one of the 281 European basketball players who won a medal during the analysed period (2000-2019). We collected data from the archive page of FIBA. Our goal was to see whether there was a relation between the youth competition experience and the minutes spent in senior world events. We used the Cramer Association Coefficient, Relative Age Effect and average age were also inspected. We found that participation in the national youth tournaments is important but not the most exclusive factor of selection. There are opportunities for success in the adult national teams for players who have covered alternative sports careers – the factor of national youth experience is not exclusive. We suppose that head coaches utilize older and more experienced players on the Olympic Games, the average ages of successful Olympic medal-winner teams are higher than other world events’ medallists. Despite the fact that we were not able to find statistically proven and associative relationship between national youth recruitment eligibility and the minutes in game spent by successful adult players, further research could be gap fillers in exploring key factors in adulthood efficiency.